2010
DOI: 10.1016/j.envsoft.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Towards multi-scale integrated hydrological models using the LIQUID® framework. Overview of the concepts and first application examples

Abstract: Distributed hydrological models are valuable tools that can be used to support water management in catchments. However, the complexity of management issues, the variety of modelling objectives, and the variable availability of data require a flexible way to customize models and adapt them to each individual problem. Environmental modelling frameworks offer such flexibility; they are designed to build and run integrated models on the basis of reusable and exchangeable components. This paper presents the LIQUID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…3.2, a probability of submersion is assigned to every road cut by combining the flooding susceptibility level of the road section and the return period of stream discharge in the river section. The CVN (Cevenne) distributed hydrological model (Vannier et al, 2016;Branger et al, 2010;Viallet et al, 2006) is used to compute the discharge at the 738 road cuts identified in the Alès case study in hourly time steps for the 2002 flash flood. The CVN model is especially developed for simulating hydrological responses in flash flood events in the Cévennes region (south of France).…”
Section: Road Network Sensitivity To Floodingmentioning
confidence: 99%
“…3.2, a probability of submersion is assigned to every road cut by combining the flooding susceptibility level of the road section and the return period of stream discharge in the river section. The CVN (Cevenne) distributed hydrological model (Vannier et al, 2016;Branger et al, 2010;Viallet et al, 2006) is used to compute the discharge at the 738 road cuts identified in the Alès case study in hourly time steps for the 2002 flash flood. The CVN model is especially developed for simulating hydrological responses in flash flood events in the Cévennes region (south of France).…”
Section: Road Network Sensitivity To Floodingmentioning
confidence: 99%
“…In agreement with the hypothesis testing framework, most of the models used in our study are developed within modelling frameworks, such as JAMS (Jena Adaptable Modelling System) (Kralisch et al, 2007) and LIQUID (Viallet et al, 2006;Branger et al, 2010). These modelling tools allow us to build "à la carte" models and to incrementally assess the impact of changing one hypothesis, either in terms of process representation or in terms of parameter specification.…”
Section: Introductionmentioning
confidence: 99%
“…This is for instance the case in West Java, Indonesia; Dhaka, Bangladesh; and Beijing, China (Braadbaart and Braadbaart, 1997;Hoque et al, 2007;Zhou et al, 2012). Large-scale hydrological models have become increasingly popular in assisting water resources management of large aquifer systems (Casper and Vohland, 2008;Goderniaux et al, 2009;Branger et al, 2010). However, great challenges exist in developing and validating such models mainly due to data issues such as unevenly distributed monitoring sites or simply insufficient data (van der Linden and Woo, 2003;Cao et al, 2006;Ferguson and Maxwell, 2010).…”
Section: Introductionmentioning
confidence: 99%